Teaching and learning Jewish history in the 21st century: New priorities and opportunities. Issue 2 (3rd April 2018) - Jacobs, Benjamin M.
ABSTRACT: New 21st-century circumstances in the Jewish world—including the changing nature of Jewish identification, the retreat from identity and continuity as singular aims of Jewish education, the democratization of Jewish learning opportunities, increased emphasis on informal and experiential Jewish education activities, and demonstrable interest among contemporary Jews in Jewish history and culture—combined with new developments in the teaching of history—including new ways to organize subject matter, account for student interest and perspective-taking, and develop disciplinary skills—create the potential to grow the field of Jewish history education in fresh and imaginative directions.